Addressing Fire Risks in High-Rise Buildings in Dhaka, Bangladesh: Strategies for Safety and Prevention (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
High-rise buildings, while equipped with modern amenities, face significant fire safety challenges due to their height, complex designs, uses and diverse materials. Fire incidents, whether accidental or intentional, can lead to devastating consequences, including loss of life, extensive property damage, and environmental impact. This study examined various fire incidents in high-rise structures and utilized Failure Mode and Effects Analysis (FMEA) to pinpoint the underlying causes. Key factors identified include electrical malfunctions, improper cooking or hot work, hazardous household chemicals, and combustible materials. The analysis also highlights systemic issues such as inadequate emergency preparedness, design flaws, and administrative shortcomings like insufficient training and poor maintenance. To reduce fire risks in high-rise buildings, it is essential to enforce the Fire Prevention and Extinguishing Act, 2003 of Bangladesh and adhere to the Bangladesh National Building Code (BNBC), 2000.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 14(1), 2025, P 77-85